(untitled) (Quaestiones Disputatae: temas en debate, 2020)
The times of the static society have come to an end, the limits and barriers of knowledge are no longer a problem, mobilizing around the world is very simple. Liquid modernity brings with it imminent changes in human beings, their behaviour and thought; dogmas are gradually disappearing, and with them, the social structures that had been consolidated some time ago, and as time goes by the behaviour of individuals and the mobilisation of societies is more difficult to predict, reaching a point of total uncertainty as to what will happen next. The value system is crumbling, people’s ideas change along with their behaviour, even to the point of leaving aside those facets that the classics considered natural and necessary in human beings for their survival. Consequently, this work seeks to determine the impact that liquid life has had on some of the most important values for human coexistence, and how consumer media manipulate our emotions through streaming media to distance us from society and make us even more consumers.